Norwegian scabies - rare case of atypical manifestation - Karina Corrêa Ebrahim; Júlia Barazetti Alves; Lísias de Araújo Tomé; Carlos Floriano de Moraes; Arianne Ditzel Gaspar; Karin Fernanda Franck; Mohamad Ali Hussein; Lucas Raiser da Cruz; Leonardo Duque Ebrahim; Luis Felipe de Oliveira Sidney (Sociedade Brasileira de Dermatologia, 2016)
Abstract Human scabies affects all social classes and different races around the world. It is highly contagious, but the exact figures on its prevalence are unknown. A 19-year-old male patient was admitted to the emergency room reporting fever (38°C) and multiple lesions throughout the body, except face, soles, and palms. Lesions were non-pruritic, which hampered the initial diagnostic suspicion. Skin biopsy was performed, and the final diagnosis was crusted scabies (Norwegian). It was concluded that human scabies is a significant epidemic disease, due to its different clinical manifestations, and because it is extremely contagious.